Uma avaliação das políticas federais de habitação no Brasil 1964/2011: déficit, demanda e habitação de interesse social - Santos, Luiz Fernando Pereira dos (2012)
This study aims to analyze the effects of federal housing policies between 1964 and 2011, particularly in the low-income population and Social Interest Housing, trampling on the historical research and literature and with the support of quantitative research deficit and housing demand. The main conclusions of this work are three. First, the period between the creation of the Housing Financial System and the end of National Housing Bank was marked by the inability to minimally meet this stratum of the population. Second, the immediate aftermath was marked by a hiatus in housing policy, contributing to the deterioration of the housing deficit. Third, despite the institutional advances of National Housing Policy, the launch of a program to stimulate construction in response to international crises and internal factors, far from solving the problem of housing deficit in the low-income population and produce social interest housing, on the contrary, was more aligned with the interests of the private sector, in particular the construction sector. In this current scenario, the housing deficit in the central low-income population will have an almost negligible improvement and another federal housing policy is doomed to failure in solving this chronic problem